Two-equation method for heat transfer efficiency in metal honeycombs: An analytical solution. (June 2016) - Liu, H.; Yu, Q.N.; Zhang, Z.C.; Qu, Z.G.; Wang, C.Z.
Highlights: Two-equation effective medium model is proposed and solved analytically. Finite element simulation results are used to validate the accuracy of the model. The influence of different factors on the heat transfer performance are examined. Abstract: An analytical model based on the two-equation method is proposed in this study to evaluate the heat transfer performance in sandwiched metal honeycomb heat exchangers under forced convection conditions. The local thermal non-equilibrium between a cooling fluid and solid honeycombs is considered. The validity and the accuracy of the analytical results are verified by numerical simulation. Compared with the convectional corrugated wall, effective medium, and transfer matrix models, the present analytical predictions are closer to the finite element simulation results in a wide range of relative density. According to the analytical solutions, the effects of cell wall length, relative thickness of the heat exchanger, fluid-to-solid thermal conductivity ratio on flow characteristics, and heat transfer performance are subsequently examined to obtain the optimum design for compact heat exchangers that require high heat transfer performance. Results show the mutual influence between cell wall length and relative thickness. The use of a metal honeycomb in compact heat exchangers can significantly enhance heat transfer with a low pressure drop.